Primary Malignant Neuroendocrine Tumour of Pleura: First Case Report - Anirban Das; Abhishek Pratap (Case Reports in Oncological Medicine)
Metastatic tumours of pleura are the most common malignant tumours causing malignant pleural effusion. Lungs are the most common primary sites. Primary pleural tumours are rarely seen and diffuse malignant mesothelioma is the most common malignant tumour of pleura. Primary malignant neuroendocrine tumour of pleura is not reported in the literature. Here, we report a rare case of primary malignant neuroendocrine tumour of pleura in a fifty-two-year-old, nonsmoker female who presented with right-sided pleural effusion and ipsilateral, dull aching chest pain. Clinical presentations of inflammatory lesions like tuberculous pleuritis and benign and malignant neoplasms of pleura are indistinguishable; hence, fluid cytology, pleural biopsy, and immunohistochemistry are necessary for exact tissue diagnosis of the tumours, which is mandatory for correct treatment and prognostic assessment.